Pemeriksaan Golongan Darah Sistem ABO pada Masyarakat Desa Kel. Boneoge, Kec. Banawa, Kab. Donggala, Prov. Sulawesi Tengah - Astri Febriana Iffaf; Slamet Ifandi; Riskayanti Riskayanti; Enggar Enggar (Institut Teknologi dan Bisnis Semarang, 2024)
This community service was carried out in Boneoge Village, Banawa District, Donggala Regency, Central Sulawesi Province. This activity aims to increase public awareness in Boneoge Village regarding the importance of knowing blood type. The problem faced is the low public awareness regarding the availability of blood and participation in blood donation, especially in emergency situations. The methods used include free blood type examination using the Point-of-Care Testing (POCT) method and socialization about the importance of blood donation. The results of this activity showed that of the 23 participants examined, the majority had blood type B+ (39.13%), followed by blood type O+ (34.78%), A+ (17.39%), and AB+ (8.70%). This finding emphasizes the importance of ongoing education to increase public awareness about knowing blood type